Anxiety and depression in probable migraine: A population-based study. (August 2017) - Song, Tae-Jin; Cho, Soo-Jin; Kim, Won-Joo; Yang, Kwang Ik; Yun, Chang-Ho; Chu, Min Kyung
Background: Although probable migraine (PM) is common among headache sufferers, there is little knowledge of the prevalence and impacts of comorbid anxiety and depression in patients with PM. We assessed the prevalence and impact of anxiety and depression among PM sufferers in the general population. Methods: We recruited Korean individuals aged 19–69 years via stratified random sampling and assessed headache type, anxiety, and depression among them using structured interviews. Results: In a representative sample of 2695 individuals, 143 (5.3%) and 379 (14.1%) had migraine and PM, respectively. Fewer patients with PM had anxiety (17.7% vs. 30.1%, p = 0.002) and depression (8.7% vs. 16.8%, p = 0.007) compared to those with migraine. Prevalence of anxiety and depression was lower in people with PM than in those with migraine in univariable analysis, but insignificant after including headache intensity and headache frequency for adjustment. Headache frequency, headache intensity, and impact of headache were significantly higher among PM and migraine patients with anxiety and depression than among those without. Conclusions: The prevalence of anxiety and depression was lower among individuals with PM compared to those with migraine. However, they were still prevalent and associated with an exacerbation of symptoms among individuals with PM.